Prometo-te ser fiel no casamento e no swing: uma construção identitária analisada à luz do sintagma identidade-metamorfose-emancipação - Santos, Marcelo Alves dos (2010)
We started from the idea that sexuality is part of the relation individuals establish with the world, observing the current appearance of several movements in defense of a greater sexual freedom and changes facing the different ways of sexuality. The amount of value judgments inserted in what refers to sexuality goes through the biological, religious and juridical fields and is crossed by culture and language, bringing therefore a discussion about new/old ways of sexuality, as the case of Swing. In the face of this, we started to consider that people who choose living the swing practice not only put in question these values which were obtained by influence from these several fields, but also raise a discussion regarding the constitution of identity, besides giving a new meaning to sexual practice. Therefore, the research aimed at trying to understand how the identity of swing practitioners is constituted, the meaning given by them and concomitantly how they see the normative institutions and the attempts of influence over their behaviors, observing if there is or not the formation of a post-conventional identity. In order to guide our discussions, we used the theory of identity proposed by Antonio da Costa Ciampa, expressed by the syntagma of identity-metamorphosis-emancipation. As it often occurs in researches oriented by Ciampa, we also used the life history narrative methodology of study to answer the questions related to the research. Then, it was possible to identify our thematic main point, that is, the relation between sexuality and identity, on the interview with the couple Jose and Mila . By reporting their life histories, they showed the existential course of several characters who constituted their respective identities until they became swingers. By considering that the swing theme brings many other inquiries, the research also approached what is traditionally understood by marriage; the double standard of morality, which is related to the aggravated differentiation between the sexual roles of men and women; what is understood by loyalty and the social attributions of followers of the swing practice